Konstrukcija in trženje kulinarične identitete na Solčavskem - Petrič, Vesna (Svetovi (Ljubljana), 2025)
This article explores the processes of constructing and marketing regional culinary identity in the Solčava region. It examines various actors involved in the area’s tourism and gastro-nomic landscape, operating at different levels – from individual providers to the munici-pality and intermediary institutional bodies, often organized as associations and societies. Drawing on ethnographic material, the study highlights notions of tradition and its purpor-ted revitalization, as well as the emergence of new culinary initiatives in the region.
Keywords: agritourism; Alpine cuisine; alpska kuhinja; cultural anthropology; ethnology; etnologija; flavour; food; gastronomija; gastronomy; kmečki turizem; kulturna antropologija; Logar Valley; Logarska dolina; lokalni turizem; okus; prehrana; Slovenia; Slovenija; tourism; Upper Savinja valley; Zgornja Savinjska dolina